2017
DOI: 10.24200/sci.2017.4233
|View full text |Cite
|
Sign up to set email alerts
|

Near-Fault Effects on RC Buildings’ Demand in Linear and Nonlinear Analyses

Abstract: Abstract. Strong ground motions of near-fault earthquakes are mostly generated by forward-directivity effects. Forward-directivity effects develop energetic pulses particularly in horizontal velocity history of fault-normal component. The narrow-band nature of the pulses results in revealing at least two peaks on the response spectra and also increasing seismic demand especially for mid-rise and high-rise buildings.Iranian seismic code (IS 2800-14) presents the coefficient N, for considering near-fault effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Baker [17] revealed that near-fault motions increase the elastic seismic demand of structures with similar periods. Mohammadi et al [18] studied the response of structures under near-fault earthquakes and reported that the velocity pulse would lead to ineffectiveness of the structural ductility and damage of structure. Gillie et al [19] indicated that nearfault earthquakes increase the inelastic seismic demand of structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baker [17] revealed that near-fault motions increase the elastic seismic demand of structures with similar periods. Mohammadi et al [18] studied the response of structures under near-fault earthquakes and reported that the velocity pulse would lead to ineffectiveness of the structural ductility and damage of structure. Gillie et al [19] indicated that nearfault earthquakes increase the inelastic seismic demand of structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The at slabs are normally used together with the lateral force-resisting structural members like shear walls or Moment-Resisting Frame (MRF) structures [23]. Mohammad et al [24] studied two 3-D RC framed structures designed according to ACI-318-14 and IS 2800-14 codes employing Linear Response History Analysis (LRHA) as well as Non-linear Response History Analysis (NRHA) under an ensemble of 11 near-fault ground motions. The obtained results revealed that the design spectrum of IS 2800-14 was incompatible with near-fault spectra and underestimated demands in long-period ranges.…”
Section: Introductionmentioning
confidence: 99%